2016
DOI: 10.1093/mnras/stw281
|View full text |Cite
|
Sign up to set email alerts
|

The clustering amplitude of X-ray-selected AGN atz∼ 0.8: evidence for a negative dependence on accretion luminosity

Abstract: The northern tile of the wide-area and shallow XMM-XXL X-ray survey field is used to estimate the average dark matter halo mass of relatively luminous X-ray selected AGN [log L X (2 − 10 keV) = 43.6 +0.4 −0.4 erg/s] in the redshift interval z = 0.5 − 1.2. Spectroscopic follow-up observations of X-ray sources in the XMM-XXL field by the Sloan telescope are combined with the VIPERS spectroscopic galaxy survey to determine the cross-correlation signal between X-ray selected AGN (total of 318) and galaxies (about … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 80 publications
7
42
1
Order By: Relevance
“…potential causes for this bias are discussed in the following section. Our lower-luminosity bin, on the other hand, resides in lower-mass halos consistent with the quasar and other X-ray AGN samples at similar luminosities and redshifts (e.g., quasars at z ∼ 1, log L bol ∼ 45; Laurent et al 2017; X-ray AGN at z ∼ 0.8, log L bol ∼ 44.9 and z ∼ 0.42, log L bol ∼ 45.2; Mountrichas et al 2016;Krumpe et al 2012), although the errors on our measurement are large. This indicates that there are also redshift and luminosity dependencies on the effective host halo masses found for AGN, due to both the growth of structure over cosmic time, as well as the scaling relations between supermassive black holes and their galaxies.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…potential causes for this bias are discussed in the following section. Our lower-luminosity bin, on the other hand, resides in lower-mass halos consistent with the quasar and other X-ray AGN samples at similar luminosities and redshifts (e.g., quasars at z ∼ 1, log L bol ∼ 45; Laurent et al 2017; X-ray AGN at z ∼ 0.8, log L bol ∼ 44.9 and z ∼ 0.42, log L bol ∼ 45.2; Mountrichas et al 2016;Krumpe et al 2012), although the errors on our measurement are large. This indicates that there are also redshift and luminosity dependencies on the effective host halo masses found for AGN, due to both the growth of structure over cosmic time, as well as the scaling relations between supermassive black holes and their galaxies.…”
Section: Discussionsupporting
confidence: 80%
“…We selected the AGN in XMM-XXL-north with spectroscopic redshifts in the DR12 BOSS footprint. While the incompleteness of the spectroscopic redshifts affects the clustering on small angular scales (< 0.03 deg; Mountrichas et al 2016), this effect is small for the projected scales that we are interested in at the effective redshifts of our samples (z ∼ 0.7 and z ∼ 1.8, corresponding to 0.9 and 1.2 Mpc h −1 , respectively). The integrated sensitivity curves are shown in Figure 1 (Georgakakis et al 2008).…”
Section: Xmm-xxlmentioning
confidence: 92%
“…This is highlighted by the use of large values of π max 200 h −1 Mpc (Georgakakis et al 2014;Allevato et al 2016) versus studies with only spectroscopic redshifts with π max 100 h −1 Mpc (e.g. Coil et al 2009;Allevato et al 2011;Mountrichas et al 2016). Therefore, we select only Pdfs based on the following quality criteria: the comoving distance separation between the z min and z max may not exceed a critical value of ∆d = 100 h −1 Mpc.…”
Section: Generalized Estimatormentioning
confidence: 99%
“…This figure compares the observed r-band magnitude distribution of the sample of the XMM-XXL AGN presented by Georgakakis et al (2017a) in the photometric or spectroscopic redshift interval 0.6 < z < 1.0 with that predicted from the simulation. The magnitude limit r < 22.5 mag is applied to the XXM-XXL AGN light cone to mimic the spectroscopic follow-up selection of the Mountrichas et al (2016) sample.…”
Section: Appendix B: Light-cone For Vipers Galaxies and Xmm-xxl Agnmentioning
confidence: 99%
“…For the latter the observational and model histograms are normalised to the same area. The simulations corresponding to the Mountrichas et al (2016) sample (Appendix B) are shown on the left. These are compared with the redshift distribution of the AGN sample presented by Mountrichas et al (2016) in the interval of the mock light-cone z ≈ 0.6 − 1.0.…”
Section: Appendix E: Redshift Distributions Of Mock Agnmentioning
confidence: 99%